Successful repair of iatrogenic inferior vena cava injury during cardiac surgery. (March 2015) - Narayan, P; Das, D; Saha, A; Das, M
Iatrogenic injury to the supra-diaphragmatic inferior vena cava (IVC) is uncommon, but can lead to a potentially complicated situation. Injury to the IVC is encountered usually during re-operative and congenital surgery, but can occur during the course of routine cardiac surgery as well. Depending on the mechanism, injury may involve the anterior or posterior wall of the IVC. A short adherent IVC, redo surgery and female sex are incremental risk factors for injury. Control of bleeding, adequate exposure and prevention of extension of the tear are the important considerations at the time of repair. While a number of management techniques have been reported, we describe a very simple maneuver that allows swift control of bleeding, adequate exposure and minimizes the risk of further extension and a satisfactory repair.